IMPROVING ERP ACCEPTANCE AT NIRWANA YUDHA TEKNIK USING THE UTAUT MODEL - Irfan Mauhibi; Leo Aldianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
In the Industry 4.0 era, digital transformation is crucial for organizations to stay competitive and enhance operational efficiency. Enterprise Resource Planning (ERP) systems, such as Trexa adopted by Nirwana Yudha Teknik, an Indonesian oil and gas company, in 2020, are central to this transformation. Trexa was designed to integrate core business functions like inventory, procurement, and project management, but it faced challenges in user adoption, with employees continuing to rely on manual tools. This research aimed to identify factors influencing the acceptance and use of the Trexa system and to propose strategic solutions for enhancing its implementation. The study employed the Unified Theory of Acceptance and Use of Technology (UTAUT) model, focusing on Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions. A quantitative approach was used, surveying 47 employees, with data analyzed through PLS-SEM. The results showed that Performance Expectancy and Effort Expectancy positively influenced Behavioral Intention to use Trexa, but Social Influence did not significantly affect user motivation. Facilitating Conditions had the strongest effect on actual usage. Based on the ADKAR model, recommendations include improving IT infrastructure, aligning processes, enforcing digital policies, and offering targeted training. This study contributes to the UTAUT framework and ERP adoption strategies.